(untitled) (Journal of the College of Basic Education, 2022)
One of the most prominent features of our present age is scientific and technological progress and the explosion of knowledge in various fields of life. The era of science and technology has been characterized by the dominance of the scientific method over human thinking and work. There are lessons in the field of grammar and literature, and it is necessary to conduct a continuous evaluation of the teaching staff on an ongoing basis and to know their capabilities and abilities to keep pace with that development and progress, whether in performance or in the possession of skills. To possess the skills of the twenty-first century, which contribute to achieving a kind of scientific progress and investing in time and effort, the researcher chose a group of schools in a random manner, and took a number of male and female teachers of these schools to achieve a ratio of (22/0), i.e. by (24) male and (33) male schools And evaluate them according to the questionnaire prepared by the researcher, which consists of (12) skills that represent the skills of the twenty-first century for the purpose of evaluation in the variable of gender and scientific experience, and After the results of the study, the researcher recommended the following: 1. Increasing the number of training courses for male and female teachers of the Arabic language and informing them of modern methods and methods in teaching Arabic language. .2 The necessity for school administrations to pay attention to libraries as a center for knowledge and culture, and to enrich them with modern books. 3. Keeping abreast of developments in the field of knowledge by male and female teachers.